THE ANALYSIS OF SIGNIFICANCE DIFFERENCE IN WRITING ACHIEVEMENT AMONG THE STUDENTS WHO ARE INTROVERT, EXTROVERT, AND AMBIVERT - Yashori Revola; Alamsyah Harahap; Bambang Suwarno (Universitas Bengkulu, 2016)
The objective of this research was to investigate significant difference among personality types in students’ writing achievement. The samples of the research comprised the third semester students of English Department of IAIN Bengkulu, academic year 2015/2016. The research design was ex - post facto. The result showed that the comparison result of writing achievement between introvert and extrovert types showed that Sig < ?, thus the alternative hypothesis was accepted. Comparison between introvert and ambivert types showed that Sig < ?, thus the alternative hypothesis was accepted. Then, comparison between extrovert and ambivert types showed Sig > ?, thus the alternative hypothesis was rejected. In conclusion, there was significance difference in writing achievement between introvert and both of extrovert and ambivert types. Meanwhile there was no significant difference in writing achievement between extrovert and ambivert types. This means that introvert students were stronger than extrovert and ambivert students in writing achievement of narrative text